2001
DOI: 10.1021/jp003736r
|View full text |Cite
|
Sign up to set email alerts
|

Heteropoly Acid-Incorporated TiO2 Colloids as Novel Photocatalytic Systems Resembling the Photosynthetic Reaction Center

Abstract: TiO 2 colloids are very useful photocatalytic systems, capable of converting solar energy to chemical or electrical energy and environmental cleaning. The key step in enhancing photocatalytic efficiency is improving photoinduced interfacial electron transfer like plant photosynthesis. It remains difficult to modify TiO 2 particles as a real analogue of the photosynthetic reaction centers of green plants. We attempted to incorporate a photoreactive heteropoly acid (HPA) such as H 3 PW 12 O 40 into TiO 2 colloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(87 citation statements)
references
References 42 publications
2
82
2
1
Order By: Relevance
“…5-8 cm´1 compared to the values of pure HPW 12 . This shift was much the same as that observed when HPW 12 was interacting with TiO 2 in a colloidal solution [31]. The system was 20 times more active than the same system without titanium for the photodegradation of methyl orange [29] (see below a detailed explanation of the mechanism of this reaction).…”
Section: Synthesis Of Tungstic Keggin Species or Their Salts In/on Zesupporting
confidence: 68%
“…5-8 cm´1 compared to the values of pure HPW 12 . This shift was much the same as that observed when HPW 12 was interacting with TiO 2 in a colloidal solution [31]. The system was 20 times more active than the same system without titanium for the photodegradation of methyl orange [29] (see below a detailed explanation of the mechanism of this reaction).…”
Section: Synthesis Of Tungstic Keggin Species or Their Salts In/on Zesupporting
confidence: 68%
“…HPB possesses adsorption in the visible light region (400-800 nm), which results from d-d and/or intervalence charge-transfer band excitation [23]. Recently, the photo-activity of HPB under visible light has attracted much attention, and HPBs have shown visiblelight photocatalytic activity in some reactions [24][25][26].…”
mentioning
confidence: 99%
“…[49] Tachikawa et al [50] experimentally demonstrated the one-electron oxidation and reduction processes reported in Figure 4 in the HPA-mediated TiO 2 photocatalytic reaction by using the two-color two laser flash photolysis technique. [50] The efficiency of this electron transfer increased by using PW 12 O 40 3-instead of SiW 12 O 40 4-.…”
Section: Hpa Supported On Different Oxidesmentioning
confidence: 99%